The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/jpm14010083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Extracorporeal Shockwave Therapy (ESWT) to Platelet-Rich Plasma (PRP) among Patients with Rotator Cuff Partial Tear: A Prospective Randomized Comparative Study

Shu-Jui Kuo,
Yu-Hsiang Su,
Shih-Chan Hsu
et al.

Abstract: A rotator cuff tear is a prevalent ailment affecting the shoulder joint. The clinical efficacy of combined therapy remains uncertain for partial rotator cuff tears. In this study, we integrated extracorporeal shockwave therapy (ESWT) with platelet-rich plasma (PRP) injection, juxtaposed with PRP in isolation. Both cohorts exhibited significant improvements in visual analogue scale (VAS), Constant–Murley score (CMS), degrees of forward flexion, abduction, internal rotation, and external rotation, and the sum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The most common injections include platelet-rich plasma (PRP) and hyaluronic acid (HA) [8,9]. These modalities can also be accompanied by extracorporeal shockwave therapy (ESWT) to increase hypervascularity [10]. A study by Maman et al (2009) found that patients older than 60 have a 54% deteriorating rate compared to younger patients with a 17% deteriorating rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…The most common injections include platelet-rich plasma (PRP) and hyaluronic acid (HA) [8,9]. These modalities can also be accompanied by extracorporeal shockwave therapy (ESWT) to increase hypervascularity [10]. A study by Maman et al (2009) found that patients older than 60 have a 54% deteriorating rate compared to younger patients with a 17% deteriorating rate [11].…”
Section: Introductionmentioning
confidence: 99%